Indonesia’s Economic Advancement through Leveraging the Geopolitical Rivalry and Geostrategic between the USA and China in the Indo-Pacific Region - Ibrahim, Muhamad Rizal; Sukandar, Rudi; Nusantari, Lusita Astuti (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2023)
Indonesia's challenge in leveraging the USA-China rivalry for economic advancement requires a nuanced approach, considering its passive foreign policy, strategic dependence, and domestic development challenges. The country aims to enhance recovery prospects by strengthening food and financial security, rebuilding regional growth, and connectivity, while also accelerating the transformation towards an inclusive and participatory digital economy. The study aims to explore how Indonesia can strategically leverage the USA-China rivalry in the Indo-Pacific to enhance its economic opportunities and examine the implications of the rivalry on its economic growth and development. This study employs a qualitative research design, analyzing, and interpreting data from literature reviews. The results show Indonesia's economic growth and development are intricately linked to its approach to leveraging the USA-China rivalry, managing infrastructure dependencies, and promoting the digital economy. To ensure sustainable progress and poverty reduction, well-designed policies and a multi-pronged approach are essential. Balancing relations with both the USA and China will be pivotal in attracting investment and expanding trade while avoiding undue external influence. Emphasizing digital infrastructure, talent, economy, and government sectors can also enhance the digital economy and contribute to Indonesia's long-term success on the global stage. Finally, Indonesia must navigate geopolitical complexities, its passive foreign policy, and domestic challenges to fully capitalize on the benefits of the USA-China rivalry while safeguarding its interests and promoting regional stability.